Evaluation of the Move 2 Learn program, a community-based movement and pre-literacy intervention for young children. (2nd January 2020) - Bedard, Chloe; Bremer, Emily; Cairney, John
ABSTRACT: Background : The Move 2 Learn (M2L) program is an evidence-based intervention designed to improve movement and pre-literacy skills in children ages 1.5–6 years. Purpose : The objective of the current study was to evaluate the effectiveness of the intervention as delivered by non-experts in a community-based setting. Methods : Staff from four community centers were trained to implement M2L. Two sites were evaluated using a quasi-experimental design and the remaining two were evaluated using a pre–post design. Movement and pre-literacy skills were assessed twice in all children. Implementation fidelity was assessed using a weekly checklist and through site-visits. Results : Thirty-one children (15 girls and 16 boys; age range 23–53 months) participated in the study. The results of the quasi-experimental study ( n = 17) showed that there was an overall effect of the program on time 2 total gross motor scores (standardized beta = 1.3, p < .05) but not pre-literacy scores, specifically print or alphabet knowledge. The pre–post design ( n = 14) showed significant change over time for total gross motor scores (Cohen's d = 1.78) and print knowledge (Cohen's d = 1.76). Conclusions : Overall, the M2L program seems to have had a positive impact on participants when delivered in a community setting by trained, non-expert leaders. Future research will need to evaluate the effectiveness of the program delivered by various educators in larger and more diverse samples of children, using more robust research designs, and to determine whether there is long-term effect of M2L on health and academic outcomes in children.